Adams and Victor's principles of neurology - Ropper, Allan H.; Samuels, Martin A.; Klein, Joshua
"The definitive text on the full spectrum of neurology presented in full color and better than ever! Long considered the field's gold-standard text, Adams and Victor's Principles of Neurology provides the very latest treatment and management strategies needed to confidently handle both common and rare neurologic conditions. Presented in full color, this classic resource meets the needs of the seasoned professional or the aspiring clinician, and has been hailed as the most detailed, thorough, and authoritative text on the subject. Reviewers have favorably compared the book's consistent, single voice to consulting with an experienced senior colleague. The latest scientific research is included in just the right amount of detail to serve as a clinical reference or a starting point for additional learning. The text is logically divided into six sections: The Clinical Method of Neurology; Cardinal Manifestations of Neurologic Disease; Growth and Development of the Nervous System in the Neurology of Aging; Major Categories of Neurologic Diseases; Diseases of the Spinal Cord, Peripheral Nerve, and Muscle; Psychiatric Disorders"--
"The wise application of science, evidence from trials, and the traditional virtues of the neurological history and examination are the main purpose of this edition of Principles of Neurology"--
Includes bibliographical references and index.
Keywords: Nervous system; Neuropsychiatry; MEDICAL / Neurology